Finite Element Analysis of Stress in Anterior Prosthetic Rehabilitation with Zirconia Implants with and without Cantilever - Tsumanuma, Karina Tiemi Sanomya; Caldas, Ricardo Armini; Silva, Isaias Donizeti; Miranda, Milton Edson; Brandt, William Cunha; Vitti, Rafael Pino (European Journal of Dentistry, 2021)
Objectives The aim of this study was to evaluate using finite element analysis (FEA), the stress distribution in prostheses (lithium disilicate crowns) on monotype zirconia implants with and without cantilever in the anterior region of the maxilla.Materials and Methods From a virtual reconstruction of bone model of the toothed maxilla from a computed tomography, three models (groups) were created: Zr (11–21)—implants placed in the area of 11 and 21 with cantilever; Zr (12–22)—implants placed in the area of 12 and 22 without cantilever; and Zr (11–22)—implants intercalated placed in the area of 11 and 22. In all models, monotype zirconia implant (4.1 × 12.0 mm) was used in single-body configuration. Lithium disilicate crowns were designed on the implants and pontics for all groups. A 150-N load was applied to the prostheses. The materials used were considered isotropic, homogeneous, and linearly elastic. FEA was performed to evaluate the maximum (tensile) and minimum (compressive) principal stresses in the implant, crowns, and bone tissue. Data were analyzed qualitatively and quantitatively.Results For all groups, the highest maximum principal stress occurred in the palatal cervical area of the implant, with the high values for the Zr (12–22) group and the low values for the Zr (11–21) group. The maximum principal stress was concentrated in the cervical palatal area of the crown, with the Zr (11–21) group presented the highest values and the Zr (12–22) group showed the lowest values. In the bone tissue all the groups presented similar values of maximum and minimal principal stress, with the palatal (maximum principal) and vestibular (minimum principal) close to the cervical of the implants the area with the highest concentration of stresses.Conclusions The position of monotype zirconia implant did not interfere in the bone tissue stress, and the implants placed in the 11–21 present lower stress in implants and higher in the crown. The cantilever does not increase the stress in the implants, crown, and bone tissue.
Keywords: zirconia implants; cantilever; finite element analysis; rehabilitation